Pengembangan Media Interaktif ICT Untuk Meningkatkan Hasil Belajar Matematika - Susanti, Lina (Journal of Innovation in Teaching and Instructional Media, 2025)
This study aims to develop interactive learning media based on ICT (Information and Communication Technology) that is effective in improving elementary school students' mathematics learning outcomes. The research method used is the research and development model with the ADDIE approach. The subjects of the study were fifth grade students at an elementary school in the Banyuasin III region. The results of the study showed that the ICT-based interactive media developed had high validity based on the assessment of material experts and media experts. The implementation of media in mathematics learning showed a significant increase in student learning outcomes, as evidenced by limited trials and field tests. Student responses to the media were also very positive, with indicators of high enthusiasm and ease in understanding the material. In conclusion, this ICT-based interactive media is effective as a mathematics learning aid, and can improve student learning outcomes and motivation. This study recommends the use of similar media in learning in elementary schools to support the implementation of the Merdeka Curriculum.